New species and new record of Neotropical Metatrichia Coquillett (Diptera: Scenopinidae) - Ale-Rocha, Rosaly; Limeira-De-Oliveira, Francisco (Zootaxa, 2021)
Two species of the genus Metatrichia Coquillett, from South America, are described as new to science: Metatrichia barbata sp. nov. and Metatrichia brunneipennis sp. nov. Their relationships with related species are discussed. Metatrichia bulbosa (Osten Sacken, 1877) is registered to Brazil for the first time. A key to New World species of Metatrichia is presented.